Highly Active and Durable Ordered Intermetallic PdFe Electrocatalyst for Formic Acid Electrooxidation Reaction - Kang, Yun Sik; Choi, Daeil; Cho, Jinwon; Park, Hee-Young; Lee, Kug-Seung; Ahn, Minjeh; Jang, Injoon; Park, Taehyun; Ham, Hyung Chul; Yoo, Sung Jong (AMER CHEMICAL SOC, 2020)
In this paper, we report the preparation of a highly active and durable ordered intermetallic PdFe catalyst supported on carbon black for formic acid oxidation reaction (FAOR) by high-temperature heat treatment under a reductive atmosphere. We found that the ordered intermetallic PdFe catalyst exhibited considerably better catalytic activity and durability toward FAOR than the disordered PdFe and pure Pd catalysts because of the high alloying degree between Pd and Fe, which induced a downshift of the Pd d-band center and structural modifications that formed a superlattice crystalline structure with Pd surface segregation. We analyzed the improved catalytic properties of the ordered intermetallic PdFe catalyst through various electrochemical analyses such as cyclic voltammetry, CO oxidation methods, chronoamperometry, physicochemical analyses such as X-ray photoelectron spectroscopy, and synchrotron radiation methods such as X-ray absorption spectroscopy. Density functional theory calculation verified the improved FAOR activity of the ordered intermetallic PdFe catalyst. In addition, a single cell based on the ordered intermetallic PdFe catalyst was also fabricated and exhibited enhanced cell performance compared to those based on the other catalysts. To the best of our knowledge, this is the first study on the preparation of an ordered intermetallic PdFe catalyst for FAOR with real single-cell application in direct formic acid fuel cells (DFAFCs). We believe that our results will be helpful for the development of highly active and durable Pd alloy catalysts for FAOR and the commercialization of DFAFC.
Keywords: FUEL-CELLS; ELECTRONIC-STRUCTURE; CO2 REDUCTION; OXIDATION; ALLOY; CATALYSTS; SURFACE; NANOPARTICLES; DECOMPOSITION; PALLADIUM